If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 11)(x + 5) = 0 Reorder the terms: (11 + x)(x + 5) = 0 Reorder the terms: (11 + x)(5 + x) = 0 Multiply (11 + x) * (5 + x) (11(5 + x) + x(5 + x)) = 0 ((5 * 11 + x * 11) + x(5 + x)) = 0 ((55 + 11x) + x(5 + x)) = 0 (55 + 11x + (5 * x + x * x)) = 0 (55 + 11x + (5x + x2)) = 0 Combine like terms: 11x + 5x = 16x (55 + 16x + x2) = 0 Solving 55 + 16x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (11 + x)(5 + x) = 0Subproblem 1
Set the factor '(11 + x)' equal to zero and attempt to solve: Simplifying 11 + x = 0 Solving 11 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + x = 0 + -11 x = 0 + -11 Combine like terms: 0 + -11 = -11 x = -11 Simplifying x = -11Subproblem 2
Set the factor '(5 + x)' equal to zero and attempt to solve: Simplifying 5 + x = 0 Solving 5 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + x = 0 + -5 x = 0 + -5 Combine like terms: 0 + -5 = -5 x = -5 Simplifying x = -5Solution
x = {-11, -5}
| 3x+19=-57-8x | | -7(2+8)/5+9(-2)= | | 9x+26=3x+98 | | 3y-4x=26 | | 2+5x=7x | | 4x^2+3+9=0 | | 9x+x+5=55 | | 2sinx-1=o | | 6(4x-1)=210 | | T(t)=5t^4-2t^3+2t | | 2x=8*8 | | X^2+y^2-6x+16+57=0 | | 3w^2+2w-14=0 | | 6+7x+1=28 | | f(-4)=4x^2-9 | | 2(4)+2(2)h+2(2)h=32 | | 8(X_5/2)=3 | | m=(b+rm)(1+t) | | a^1/4b^2*a^2/3b^1/4/a^1/2b^1/8 | | -2x=-6x+12 | | 13(6c-8)=8c-2 | | 7x-6=-7x-160 | | 5x-3(2x-1)=4/7 | | x+(x-0.12)*1.5*0.65=0.183 | | -16x^2+72x+7=0 | | 3x-9=-5x+47 | | 0.04x+0.01(480-x)=0.1 | | 8x+27=2x+147 | | 5(x-12)+15=(3+x) | | 4x+90+2x=180 | | Y=sqrt(16x-32) | | -10x+2+7x=-37 |